Pengkayaan Vitamin C Pada Pakan Silase Keong Mas (Pomacea canaliculata): Efek Terhadap Biomassa Dan Reproduksi Artemia sp. Skala Labolatorium - Pramesty, Nur Ifada; Rosyida, Eka; Nilawati, Jusri (Universitas Tadulako, 2023)
Giving vitamin C to feed is very necessary considering that vitamin C is a multivitamin needed by the body. The purpose of this study was to determine the proper dose of vitamin C in the golden snail silage feed in increasing the biomass and reproduction of Artemia sp. The research was conducted at the Laboratory of Water Quality and Aquatic Biology, Department of Fisheries and Maritime Affairs, Faculty of Animal Husbandry and Fisheries, Tadulako University. The variables observed were population density, egg/cyst production, hatching rate, survival rate (SR), water quality. The study used a completely randomized design (CRD) with 5 treatments and 4 replications with 20 experimental units A: control , B: vitamin C 12 mg/L, C: vitamin C 18 mg/L, D: vitamin C 24 mg/L, E: vitamin C 30 mg/L. The results showed that vitamin C enrichment with a concentration of 24 mg/L had a very significant effect (p<0.05) on each variable. Improper concentration of vitamin C in feed enrichment can affect the survival of Artemia sp.